The Mythological World in the Literary Texts of the Turkic-speaking Peoples: Book review of: Sharyafetdinov, R.Kh. (2021). Mythopoetics of Tatar literature: Monograph. Moscow, Berlin, Direct-Media - Irina A. Tairova (RUDN Journal of Studies in Literature and Journalism, 2021)
The review of the monograph by R.Kh. Sharyafetdinov "Mythopoetics of Tatar Literature" deals with new developments in the field of mythopoetics, based on Tatar artistic material. The mytho-religious approach of the researcher is analyzed, which makes it possible to study at a deep level the influence of cultural, philosophical, and religious realities on Tatar literature. For this purpose, the author of the scientific work examines the Tatar cosmogonic ideas, the mythologism of the plant and animal worlds in the works of Kul Gali, Mukhammedyar, G. Kandaly; Dardmend, G. Tukay, F. Burnash, N. Isanbet; M. Jalil; F. Karim; M. Khabibullina, N. Fattakh, R. Kutuy, R. Faizullin; R. Zaydulla, G. Yakhina.